Open Access and the Library - Oberländer, Anja (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Libraries are places of learning and knowledge creation. Over the last two decades, digital technology-and the changes that came with it-have accelerated this transformation to a point where evolution starts to become a revolution.The wider Open Science movement, and Open Access in particular, is one of these changes and is already having a profound impact. Under the subscription model, the role of libraries was to buy or license content on behalf of their users and then act as gatekeepers to regulate access on behalf of rights holders. In a world where all research is open, the role of the library is shifting from licensing and disseminating to facilitating and supporting the publishing process itself.This requires a fundamental shift in terms of structures, tasks, and skills. It also changes the idea of a library's collection. Under the subscription model, contemporary collections largely equal content bought from publishers. Under an open model, the collection is more likely to be the content created by the users of the library (researchers, staff, students, etc.), content that is now curated by the library.Instead of selecting external content, libraries have to understand the content created by their own users and help them to make it publicly available-be it through a local repository, payment of article processing charges, or through advice and guidance. Arguably, this is an overly simplified model that leaves aside special collections and other areas. Even so, it highlights the changes that research libraries are undergoing, changes that are likely to accelerate as a result of initiatives such as Plan S.This Special Issue investigates some of the changes in today's library services that relate to open access.